Teaching English Words’ Literal Meaning To 2nd Semester Students of FKIP UBL Through Stage Hypnosis - Helta Anggia (Bandar Lampung University (UBL), 2014)
This study reviewed the use of stage hypnosis in teaching students English words meaning. Memorization is one principle in mastering vocabulary that takes a quiet interval until someone really owns words (Thornbury, 2002). To reduce study time problem, the researcher applied a suggestive principle, teaching students by inserting positive suggestion. In this case, stage hypnosis, part of hypnotism, was provided as a solution to that study time problem. The positive suggestion was translated into suggesting students about literal meaning of words in English. The sample consists of four second semester students of English Study program of UBL Bandar Lampung. After the observation (pretest-treatment-1stposttest-2nd posttest), and interview to the sample, the researcher found that stage hypnosis is very significant for teaching words meaning. All sample show a significant behavioral change by unconsciously knowing the 10 difficult words’ meaning. The interview also proved their preference of this new instant technique. The second posttest was held for reliability reason. It indicated that their memory of words meaning were successfully stored in their long-term memory. Finally, the researcher concluded that stage hypnosis must be further developed for English vocabulary mastery teaching.